Replication of the Venezuelan Equine Encephalitis Vaccine from a Synthetic PCR Fragment - Christine Mathew; Colin Tucker; Irina Tretyakova; Peter Pushko (MDPI AG, 2024)
Background/Objectives: There is no approved human vaccine for Venezuelan equine encephalitis (VEE), a life-threatening disease caused by the VEE virus (VEEV). In previous studies, plasmid DNA encoding the full-length RNA genome of the VEE V4020 vaccine was used for the preparation of experimental live virus VEE vaccines in the plasmid-transfected cell culture. Methods: Here, we used the high-fidelity polymerase chain reaction (PCR) to prepare synthetic, transcriptionally active PCR (TAP) fragments encoding the V4020 genome. Results: TAP fragment initiated the replication of the V4020 live virus vaccine in TAP fragment-transfected cells. A transfection of less than 1 ug of TAP fragment resulted in the replication of the V4020 vaccine virus in CHO cells. Conclusion: We conclude that not only plasmid DNA but also synthetic PCR-generated DNA fragments can be used for the manufacturing of live vaccines for VEEV and, potentially, other viruses.